2011
DOI: 10.1007/s13181-011-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis with Latrodectus Antivenin Resulting in Cardiac Arrest

Abstract: Latrodectus mactans antivenin is a safe and effective therapy for severe black widow spider envenomations when given to most patients. We report a case of a 37-year-old male with a history of asthma that was given L. mactans antivenin for symptoms related to a black widow envenomation and developed a severe anaphylactic reaction resulting in cardiac arrest. When traditional therapies failed, the patient was given methylene blue for anaphylactic shock resulting in a 30-h period of hemodynamic stability. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Some Latrodectus venom includes proteinases and other potentially cyctotoxic components (Duan et al 2008). Latrodectus antivenom is effective against S. grossa venom -although potentially very dangerous as a treatment through anyphylaxis related to injection of sera (Graudins et al 2002;Isbister & Fan 2011;Murphy et al 2011;Garb & Hayashi 2013).…”
Section: Cytotoxicity Ulceration Necrotic Arachnidism and Putative Bacterial Carriagementioning
confidence: 99%
“…Some Latrodectus venom includes proteinases and other potentially cyctotoxic components (Duan et al 2008). Latrodectus antivenom is effective against S. grossa venom -although potentially very dangerous as a treatment through anyphylaxis related to injection of sera (Graudins et al 2002;Isbister & Fan 2011;Murphy et al 2011;Garb & Hayashi 2013).…”
Section: Cytotoxicity Ulceration Necrotic Arachnidism and Putative Bacterial Carriagementioning
confidence: 99%
“…There are several commercial antivenoms available, and the use of antivenom has been shown to decrease pain duration and severity such that discharge home is more likely [ 14 , 17 ]. Adverse events associated with the use of antivenom include anaphylaxis, serum sickness and rarely death [ 14 , 17 - 19 ]. As such, it is highly suggested that consultation with a clinical toxicologist or another widow bite expert is carried out.…”
Section: Discussionmentioning
confidence: 99%
“…11 Most reports show that BSW antivenin is well tolerated, particularly in the pediatric population. 5,6,14 In spite of these reports, antivenin is still considered to be safe and effective in rapidly relieving symptoms in cases of severe envenomation. In 1 Australian study using antivenin to the red black spider (Latrodectus hasselti), the incidence of serum sickness was 1% to 7%.…”
Section: Discussionmentioning
confidence: 99%